Serial magnetic resonance imaging of splenomegaly in the Trypanosoma brucei infected mouse - Samantha Paterson; William Matthew Holmes; Jean Rodgers (Public Library of Science (PLoS), 2022)
Splenomegaly, an enlargement of the spleen, is a known clinical sign of the parasitic disease, human African trypanosomiasis. This study follows the development of splenomegaly in a group of mice over multiple infection points, using a non-invasive imaging modality, magnetic resonance imaging (MRI). CD-1 mice infected with GVR35 T.b. brucei demonstrated a significant increase in spleen size from day 7 post-infection, with changes in the spleen tracked in individual animals over five time points. At the final time point, the mean spleen weight calculated using the spleen volume from the MR images was compared with the post-mortem gross spleen weight. No significant difference was detected between the two methods (1.62 ± 0.06g using MRI and 1.51 ± 0.04g gross weight, p = 0.554). Haematology and histological analysis were also performed, giving additional insight into splenomegaly for the GVR35 strain of infection. The study demonstrates that MRI is a useful tool when examining changes in organ volume throughout HAT infection and may be applicable in the investigation of a range of conditions where changes in organ volume occur and MRI has not been used previously. Author summary Although splenomegaly (the enlargement of the spleen) has been explored previously in mice infected with human African trypanosomiasis (HAT), a parasitic disease originating in Africa, it has never been examined in individual mice over time. This study is the first to do this using magnetic resonance imaging (MRI). By scanning mice infected with trypanosomes, we were able to examine how the spleen size and shape changed over the course of the infection. We were also able to show the enlargement in spleen size before the clinical signs became apparent, demonstrating that MRI could be useful for examining changes in the organs in the body following the onset of disease.